Preventing Seal Leak During Negative Pressure Wound Therapy Near External Fixators: A Technical Tip. Issue 3 (March 2017) - Mannino, Brian J.; Pullen, Michael W.; Gaines, Robert
Abstract : Summary: Negative pressure wound therapy is an effective tool for the treatment of open wounds. Occasionally these wounds are associated with injuries or procedures that require treatment with an external fixator. This article shows how a simple, inexpensive, and commercially available product can be used to prevent loss of suction around external fixator pins within the negative pressure wound treatment area.